The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.1590/1519-6984.260091
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of pilocarpine-induced epileptic seizures in adult male mice

Abstract: Epilepsy is one of the most common neurological disorders affecting most social, economic and biological aspects of human life. Most patients with epilepsy have uncontrolled seizures and drug side effects despite the medications. Patients with epilepsy often have problems with attention, memory, and information processing speed, which may be due to seizures, underlying causes, or anticonvulsants. Therefore, improving seizure control and reducing or changing the anti-epileptic drugs can solve these problems, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…In addition, this was what we have observed in the current results when rats were treated with PEG only, a decline of mitochondrial biogenic formation, reduce transcription, and replication of mtDNA, which ultimately causes a weakening of the mitochondrial function, this explains the decline in the mtTFA expression and PGC-1α in hepatic tissue. The toxic substances cause the impaired activity of the electron transport chain by affecting the complex second and fourth of the respiratory chain as it leads to the electrons accumulation in the chain, and thus leads to transport and interaction with oxygen to form superoxide anion radical, this causes weakness in the mitochondrial activity [32] mentioned that the acute toxicity of ethylene glycol causes mitochondrial abnormalities and this is what we observed in the current results. Diab et al [9] found that DNA damage may be the result of free radical-mediated oxidative stress.…”
Section: Resultssupporting
confidence: 80%
“…In addition, this was what we have observed in the current results when rats were treated with PEG only, a decline of mitochondrial biogenic formation, reduce transcription, and replication of mtDNA, which ultimately causes a weakening of the mitochondrial function, this explains the decline in the mtTFA expression and PGC-1α in hepatic tissue. The toxic substances cause the impaired activity of the electron transport chain by affecting the complex second and fourth of the respiratory chain as it leads to the electrons accumulation in the chain, and thus leads to transport and interaction with oxygen to form superoxide anion radical, this causes weakness in the mitochondrial activity [32] mentioned that the acute toxicity of ethylene glycol causes mitochondrial abnormalities and this is what we observed in the current results. Diab et al [9] found that DNA damage may be the result of free radical-mediated oxidative stress.…”
Section: Resultssupporting
confidence: 80%
“…The intial step in assisting patients in better controlling their condition is to improve self-care behaviors, which emphasizes the significance of efficient elements for the patient self-treatment. Self-care also enhances the effectiveness of the illness's therapy and declines the likelihood of complications [27][28][29][30][31][32][33][34][35].…”
Section: Resultsmentioning
confidence: 99%
“…Unlike normal cells, cancer cells prefer aerobic glycolysis instead of oxidative phosphorylation (OXPHOS), which is performed by lactate dehydrogenase-mediated conversion of glucose to pyruvate and produces lactic acid [12]. Rapid tumor cellular proliferation creates a nutrient-restricted TME that impairs effector T cell differentiation and function.…”
Section: Metabolismmentioning
confidence: 99%
“…Moreover, high glucose utilization by glycolysis in the tumor cells results in the production of large amounts of anaerobic metabolites such as lactate in TME. The elevated lactic acid in turn leads to acidification of TME causing TIL dysfunction by blocking lactate export, and promoting the accumulation of tolerogenic cells and MDSC infiltration favoring TME for tumor progression [12] (Fig. 2).…”
Section: Metabolismmentioning
confidence: 99%
See 1 more Smart Citation